Forward performance measurement with applications in indifference valuation - Yusong, L; Yusong Li (2014)
In this thesis, we present basic ideas and key results for forward performance measurement. Besides, we provide an explicit construction of the optimal processes of a class of time-monotone forward performance processes. Moreover, starting with a two parameter family risk tolerance function, we construct a class of forward performance processes. By letting the parameter go to zero, we obtain the forward exponential utility. Finally, using the forward exponential utility, we solve the integrated portfolio management problem by the so-called utility-based approach and compare it with its classical backward indifference counterpart.